2022
DOI: 10.1002/cbdv.202100759
|View full text |Cite
|
Sign up to set email alerts
|

Bioassay Directed Fractionation of Petroleum Ether Extract of Aerial Parts of Ceriops tagal: Isolation of Lupeol as the Nematicidal Agent against Cyst Nematode Heterodera zeae

Abstract: Plant parasitic cyst nematode Heterodera zeae is a pest, causing substantial economic losses in agriculture. Organic pesticides, based on plant products have emerged as eco-benign nematicidal agents. Ceriops tagal is a well-known marine medicinal plant which has not been evaluated against any nematode. Petroleum ether extract of the aerial parts of the plant (CTP), exhibited promising activity against infective stage larvae of H. zeae. On subjecting to classical solvent-solvent separation, it afforded petroleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“… 21 A growing number of research articles aims to identify new anthelmintics from natural sources. 22 , 23 , 24 , 25 , 26 Plant extracts are an important source of new chemical scaffolds with valuable applications for drug discovery. 27 , 28 , 29 , 30 However, the search for bioactive compounds from complex mixtures (i.e., crude extracts) remains a Herculean task.…”
Section: Introductionmentioning
confidence: 99%
“… 21 A growing number of research articles aims to identify new anthelmintics from natural sources. 22 , 23 , 24 , 25 , 26 Plant extracts are an important source of new chemical scaffolds with valuable applications for drug discovery. 27 , 28 , 29 , 30 However, the search for bioactive compounds from complex mixtures (i.e., crude extracts) remains a Herculean task.…”
Section: Introductionmentioning
confidence: 99%
“…This bark species has been used in traditional medicine to treat hemorrhage (Bandaranayake 1998). Phytochemical analysis revealed that C. tagal is rich in gallic acid, quercetin (Sachithanandam et al 2022), terpenoids (Biswas et al 2021;Zhang et al 2021;Ahmad et al 2022), and steroids (Egra et al 2023). These compounds have been shown to have various potential therapeutic applications, including antitumor (Ni et al 2018;Sachithanandam et al 2022), antibacterial (Chacha et al 2008;Egra et al 2023), antioxidant (Sachithanandam et al 2022;Egra et al 2023), antihyperglycemic, analgesic, anti-inflammatory (Biswas et al 2023), diuretic (Biswas et al 2021), immunosuppressant (Zhang et al 2021), and nematocidal (Ahmad et al 2022) activities.…”
Section: Introductionmentioning
confidence: 99%
“…Phytochemical analysis revealed that C. tagal is rich in gallic acid, quercetin (Sachithanandam et al 2022), terpenoids (Biswas et al 2021;Zhang et al 2021;Ahmad et al 2022), and steroids (Egra et al 2023). These compounds have been shown to have various potential therapeutic applications, including antitumor (Ni et al 2018;Sachithanandam et al 2022), antibacterial (Chacha et al 2008;Egra et al 2023), antioxidant (Sachithanandam et al 2022;Egra et al 2023), antihyperglycemic, analgesic, anti-inflammatory (Biswas et al 2023), diuretic (Biswas et al 2021), immunosuppressant (Zhang et al 2021), and nematocidal (Ahmad et al 2022) activities. For instance, vomifoliol, a sesquiterpene isolated from the hypocotyls extracts of C. tagal, displayed an immunosuppressant effect by inhibiting the dephosphorylation of NFAT1 and the proliferation of Jurkat cells (Zhang et al 2021).…”
Section: Introductionmentioning
confidence: 99%